Kegiatan Bimbingan Belajar Menggunakan Metode Pembelajaran Aksi (Aktif, Kreatif, Santai, dan Inovatif) di Desa Raja Timur - Ndoya, Maria Karmelita; Ndasi, Alvensiana Ayuti Ratna; Una, Yosefania; Wau, Maria Patrisia (Abdimas Indonesian Journal, 2025)
The purpose of this tutoring program is to provide tutoring to students of SD Inpres Padhapae aged 6-12 years in Raja Timur Village. The object of this study was the children of SD Inpres Padhapae. The results of this study are tutoring provided by Thematic KKN students using the AKSI method to increase children's interest in participating in learning. AKSI (active, creative, relaxed and innovative) is a strategy in teaching that creates an atmosphere in the teaching and learning process that is safe and comfortable so that the learning carried out by students is focused. The learning process carried out by teachers currently tends to be activities dominated by teachers. This tutoring program uses the AKSI method. The existence of a tutoring program can help children in the learning process such as providing guidance in the learning process that aims to be Guidance for children is focused on students at SD Inpres Padhapae, which can increase the enthusiasm and togetherness of children with students.